Glucose-6-Phosphate Dehydrogenase from the Human Pathogen Trypanosoma cruzi Evolved Unique Structural Features to Support Efficient Product Formation. Issue 11 (17th May 2019) - Ortíz, Cecilia; Botti, Horacio; Buschiazzo, Alejandro; Comini, Marcelo A.
Abstract: Glucose-6-phosphate dehydrogenase (G6PDH) is the key enzyme supplying reducing power (NADPH) to the cells, by oxidation of glucose-6-phosphate (G6P), and in the process providing a precursor of ribose-5-phosphate. G6PDH is also a virulence factor of pathogenic trypanosomatid parasites. To uncover the biochemical and structural features that distinguish Tc G6PDH from its human homolog, we have solved and analyzed the crystal structures of the G6PDH from Trypanosoma cruzi ( Tc G6PDH), alone and in complex with G6P. Tc G6PDH crystallized as a tetramer and enzymatic assays further indicated that the tetramer is the active form in the parasite, in contrast to human G6PDH, which displays higher activity as a dimer. This quaternary structure was shown to be particularly stable. The molecular reasons behind this disparity were unveiled by structural analyses: a Tc G6PDH-specific residue, R323, is located at the dimer–dimer interface, critically contributing with two salt bridges per subunit that are absent in the human enzyme. This explains why Tc G6PDH dimerization impaired enzyme activity. The parasite protein is also distinct in displaying a 37-amino-acid extension at the N-terminus, which comprises the non-conserved C8 and C34 involved in the covalent linkage of two neighboring protomers. In addition, a cysteine triad (C53, C94 and C135) specific of Kinetoplastid G6PDHs proved critical for stabilization of Tc G6PDH active site. Based on the structural and biochemical data, we posit that the N-terminal region and the catalytic site are highly dynamic. The unique structural features of Tc G6PDH pave the way toward the design of efficacious and highly specific anti-trypanosomal drugs. Graphical Abstract: Unlabelled Image